CDI m-learning. Differential and integral calculus assisted by mobile technology: interaction and communication patterns in the classroom: CDI m-learning. Cálculo diferencial e integral asistido por tecnología móvil: patrones de interacción y comunicación en el aula - Figueroa F, Nuria V. (2020)
This paper reports the results of a research project about what happens in classroom dynamics related to communication an interaction processes using mobile technology methodologies. The first objective was to show the student?s role in the learning processes when using mobile technology methodologies and the one that they perceive to be developed. In addition, we studied the teacher’s role and the one that she perceives has to play in this educational context.Results reveal organizational culture elements that can affect an educational innovation process such as incorporation of iPad as a didactic resource. This kind of course does not always respond to the student's interests what affect his (her) motivation of critical activities inside the classroom. Training teachers to develop educational innovations, such as the use of iPad into mathematics lessons, requires more than just knowing the correct handle of mobile devices, it demands working in an environment full of uncertainty. The attitudinal performance of some students may differ from the expected and they get pressure because the challenges elements of the innovation process and those stablish by the organizational culture.